Model Operet Wayang Pandawa untuk Pengenalan Bahasa Jawa pada Anak Usia Dini: Pengembangan dan Implementasi di TK ABA Karanganyar - Septika Rahmawati; Joko Pamungkas (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Javanese, as part of local cultural identity, needs to be introduced from an early age to prevent it from being eroded by the dominance of foreign languages and digital media. One relevant approach is through traditional performing arts, packaged appropriately for children's development. This study aims to develop the puppet operetta "Pandawa 5" as a learning medium for introducing Javanese to kindergarten students at ABA Karanganyar. The method used in this study was Research and Development (RnD) with the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects were 15 boys aged 5–6 years in the B2 group at ABA Karanganyar Kindergarten. This study yielded validation results, indicating that the operetta script obtained an average score of 86% (valid category). Quantitative pretest–posttest data showed a significant increase, from a score range of 30–55 in the pretest to 65–85 in the posttest, with an average increase of 35 points. All participants experienced an increase in their understanding of Javanese, demonstrated by their ability to use simple vocabulary, understand dialogue, and express the character values of wayang characters such as courage, honesty, and responsibility. Thus, this study concludes that the Wayang Pandawa 5 operetta is effective as a medium for learning Javanese in kindergarten, while also serving as a means of preserving local culture and strengthening character education from an early age